Short-Chain Fatty Acids Inhibit Oxidative Stress and Inflammation in Mesangial Cells Induced by High Glucose and Lipopolysaccharide - Huang, Wei; Guo, Heng-Li; Deng, Xian; Zhu, Ting-Ting; Xiong, Jian-Feng; Xu, You-Hua; Xu, Yong (Experimental and Clinical Endocrinology & Diabetes, 2017)
Recently, an connection between Short-chain fatty acids (SCFAs) produced by intestinal microbiota and kidney has been revealed. The aim of this study was to explore whether SCFAs or their specific G protein-coupled receptors 43 (GPR43) agonist inhibit oxidative stress and inflammatory response in glomerular mesangial cells (GMCs) induced by high glucose and lipopolysaccharide (LPS). Our research showed that treatment with SCFAs, especially acetate and butyrate, or GPR43 agonist significantly inhibited GMCs proliferation induced by high glucose and LPS, and then reversed the production of reactive oxygen species (ROS) and malondialdehyde (MDA) but increased levels of antioxidant enzyme superoxide dismutase (SOD). Furthermore, SCFAs or GPR43 agonist obviously increased the protein expression of GPR43 induced by high glucose and LPS, but diminished the expression of adhesion molecule intercellular adhesion molecule-1 (ICAM-1), and then decreased the proinflammatory cytokine monocyte chemoattractant protein (MCP-1) and interleukin-1β (IL-1β) release from GMCs stimulated by the high glucose and LPS. These combined results support the hypothesis that SCFAs or GPR43 agonist can inhibit oxidative stress and inflammation of GMCs induced by high glucose and LPS, suggesting that SCFAs induced signaling pathway may act as new therapeutic targets of diabetic nephropathy (DN).
Keywords: short-chain fatty acids; oxidative stress; inflammation; diabetic nephropathy